DAMPAK PROGRAM PENERIMAAN PESERTA DIDIK BARU (PPDB) MELALUI SISTEM ZONASI TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Ni’matul Fauziah; Hendri Handoko (Program Studi Pendidikan Matematika, FKIP Universitas Muhammadiyah Cirebon, 2020)
Abstract Education is a very important part of development. In education a process cannot be separated by the development process itself. The progress of the nation and the survival of the nation is seen from the progress or failure of an education. The Minister of Education and Culture issued a policy according to education, which initially took the form of a rayonization system to become a zoning system in the acceptance of new students. With this zoning system, it is hoped that the acceptance of new students can run without discrimination and be able to provide equal opportunities for every student to receive formal education, regardless of low cognitive or economic abilities. The purpose of this study is to determine the impact of the implementation of the student admission program on student mathematics learning outcomes and to determine the stakeholder's response to the new student admission program through the zoning system. The research method used is through the Mix Method approach (Mixed Research). The collection techniques used were interviews, questionnaires and documentation. The evaluation results show that the mathematics learning outcomes of students received through the zoning system tend not to be better than the mathematics learning outcomes of students received through the non-zoning system. Stakeholder response consisting of the information section of the education office, second curriculum, community and parents. In general, the zoning system rules must be improved starting from the distribution of zoning routes, the percentage of zoning routes and achievement pathways, then leveling the facilities and infrastructure in each school. In general, parents and the community do not agree with the zoning system rules for PPDB because parents are not free to send their children to schools which they consider to be of good quality. Keywords: Zoning, Learning Outcomes, Stakeholders Abstrak Pendidikan merupakan bagian yang sangat penting dalam pembangunan. Dalam pendidikan suatu proses itu tidak bisa dipisahkan oleh proses pembangunan itu sendiri. Kemajuan bangsa dan kelangsungan hidup bangsa dilihat dari maju tidaknya suatu pendidikan. Menteri Pendidikan dan Kebudayaan (Mendikbud) mengeluarkan kebijakan sesuai pendidikan yang mulanya berupa sistem rayonisasi menjadi sitem zonasi dalam penerimaa peserta didik baru (PPDB). Dengan adanya sistem zonasi ini diharapkan penerimaan peserta didik baru dapat berjalan tanpa diskriminasi dan mampu memberikan kesempatan yang sama bagi setiap peserta didik untuk mengenyam pendidikan formal, terlepas dari kemampuan kognitif atau ekonomi yang rendah. Adapun tujuan dalam penelitian ini yaitu untuk mengetahui dampak dari pelaksanaan program penerimaan peserta didik terhadap hasil belajar matematika siswa dan untuk mengetahui respon stakeholder terhadap program penerimaan peserta didik baru melalui sistem zonasi. Metode penelitian yang digunakan melalui pendekatan Mix Method (Penelitian Campuran). Teknik Pengumpulan yang digunakan adalah wawancara, angket dan dokumentasi. Hasil evaluasi menunjukan bahwa hasil belajar matematika siswa yang diterima melalui sistem zonasi cenderung tidak lebih baik dari pada hasil belajar matematika siswa yang diterima melalui sistem non-zonasi. Respon stakeholder yang terdiri dari bagian informasi dinas pendidikan, wakasek kurikulum, masyarakat dan orang tua. Secara umum aturan sistem zonasi harus dibenahi mulai dari pembagian jalur zonasi, besar prosentase jalur zonasi dan jalur prestasi, kemudian meratakan sarana dan prasarana disetiap sekolah. Secara umum orang tua dan masyarakat kurang setuju adanya aturan sistem zonasi terhadap PPDB dikarenakan orang tua tidak bebas menyekolahkan anaknya ke sekolah yang mereka anggap mempunyai kualitas yang bagus. Kata kunci: Zonasi, Hasil Belajar, Stakeholder